Investigasi Kekesatan Perkerasan Jalan Menggunakan Wessex Skid Tester ( Investigation of Skid resistance of Road Pavement Using the Wessex Skid Tester) - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian UGM, 2005)
ABSTRAK Skid resistance of road pavement present the resistance condition between surfaces of pavement and tire so that vehicle do not slipped whether at the time of wet or dry road surfaces. This article aim to explain the result of measurement of skid resistance of road using the Wessex Skid Tester. Statistical Analysis is made to evaluate the skid resistance level of road pavement and to compare the level of skid resistance among three types of road pavement structure in different location. Three types of structure of road pavement therewith the location successively are asphalt concrete (Kaliurang Street), concrete block (Teknika Selatan - Keselzatan-Bhineka Street) and hot rolled sheet (HRS) in Yacaranda Street. The result of analysis is level of skid resistance related to each types of road and comparison of three road structure types. Here, the rate of skid resistance of asphalt concrete, concrete block and HRS successively are 45,29 (standard deviation of 3,55), 48,18 (standard deviation of 3,57), and 60,05 (standard deviation of 6,66). Concrete block paving has the higher level of skid resistance than asphalt concrete. The level of skid resistance of HRS is higher than the concrete block caused by the HRS condition at the time of that measurement was medium damage.